Geometric Nightmare

Geometry Level 3

Diagram above shows a unit square A B C D ABCD , the line A D AD is extended to point E E such that B E BE is a straight line intersecting the line extended line of A D AD at E E with F F as a point of B F BF that is a point on line side C D CD such that F E = 1 FE = 1 . Let distance D E DE be denoted as x x . Find the value of x x .

2 1 + 2 2 1 2 \frac{\sqrt{2}-1+\sqrt{2\sqrt{2}-1}}{2} 3 + 1 + 2 3 1 3 \frac{\sqrt{3}+1+\sqrt{2\sqrt{3}-1}}{3} 2 1 + 2 2 + 1 4 \frac{\sqrt{2}-1+\sqrt{2\sqrt{2}+1}}{4} 2 2 + 2 2 + 4 2 \frac{\sqrt{2}-2+\sqrt{2\sqrt{2}+4}}{2}

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

4 solutions

Gabriel Benício
Apr 11, 2015

First, let be y = F D y=FD . As we can see, Δ F D E \Delta FDE and Δ B A E \Delta BAE are similar. Thus: y x = 1 1 + x x y = x y \frac{y}{x}=\frac{1}{1+x} \Rightarrow xy=x-y .

But, from triangle F D E FDE we can write: x 2 + y 2 = 1 x^2+y^2=1 .

Subtracting 2 x y -2xy from both sides we obtain:

( x y ) 2 = 1 2 x y ( x y ) 2 = 1 2 x y (x-y)^2=1-2xy \Rightarrow (xy)^2=1-2xy .

Now, let's call z = x y z=xy

z 2 + 2 z 1 = 0 z^2+2z-1=0 .

As we know, z = x y > 0 z=xy>0 , then z = 2 1 z=\sqrt{2}-1 .

Thus we have 2 1 = x y y = x 2 + 1 \sqrt{2}-1=x-y \Rightarrow y=x-\sqrt{2}+1

Substituting in the Pythagorean theorem: x 2 + ( x ( 2 1 ) ) 2 = 1 x^2+(x-(\sqrt{2}-1))^2=1

2 x 2 ( 2 2 2 ) x + 2 2 2 = 0 2x^2-(2\sqrt{2}-2)x+2-2\sqrt{2}=0

x 2 ( 2 1 ) x + 1 2 = 0 x^2-(\sqrt{2}-1)x+1-\sqrt{2}=0

x = 2 1 + 2 2 1 2 x=\frac{\sqrt{2}-1+\sqrt{2\sqrt{2}-1}}{2}

This is such an elegant solution, Gabriel; no quartic polynomials to worry about. :)

Brian Charlesworth - 6 years, 2 months ago

Awesome ! Thanks for posting

Karan Shekhawat - 6 years, 2 months ago

Beautiful solution to a beautiful problem .I wonder if you or Brian or anybody else tried coordinate geometry after failing by using trigonometry.I let B(0,1) and E (P,0)giving F (1,1-1/P) . EF=1 gives a quartic in P which can be reduced to a quadratic in (P+1/P)..On solving forP ,simply subtract 1 to get x.

Des O Carroll - 6 years, 2 months ago

http://postimg.org/image/r8r03o3ch/

Sanjoy Roy - 6 years, 1 month ago

backward solution: x / (x+1) = sqrt( 1-x^2 ) just substitute

First note that Δ F E D \Delta FED and Δ F B C \Delta FBC are similar. Thus

D F D E = C F C B 1 x 2 x = 1 1 x 2 1 \dfrac{|DF|}{|DE|} = \dfrac{|CF|}{|CB|} \Longrightarrow \dfrac{\sqrt{1 - x^{2}}}{x} = \dfrac{1 - \sqrt{1 - x^{2}}}{1}

1 x 2 = x 1 + x 1 x 2 = x 2 ( 1 + x ) 2 \Longrightarrow \sqrt{1 - x^{2}} = \dfrac{x}{1 + x} \Longrightarrow 1 - x^{2} = \dfrac{x^{2}}{(1 + x)^{2}}

x 4 + 2 x 3 + x 2 2 x 1 = 0. \Longrightarrow x^{4} + 2x^{3} + x^{2} - 2x - 1 = 0.

Now there is a technique for factoring quartics, but it is quite a slog so I just used WolframAlpha to confirm that the posted answer is indeed a solution to the above quartic. If anybody has a more elegant way of algebraically finding this exact value I would be most interested.

let E^=2X giving you Cotan 2X=Cos 2X+1 Solving this may give you x without having to solve the quartic

Des O Carroll - 6 years, 2 months ago

Log in to reply

How did you got this equation? Can you please elaborate!

Harshit Sharma - 6 years, 2 months ago

Log in to reply

let the angle AEB= 2X then cotan 2X =cos 2X +1

Des O Carroll - 6 years, 2 months ago

That sounds interesting, but I'm not quite sure what your terms are. Is "E^" meant to indicate D E F \angle DEF ?

Brian Charlesworth - 6 years, 2 months ago

Log in to reply

yes , just not able to write it like this on my computer

Des O Carroll - 6 years, 2 months ago

Thank you sir for Link

Karan Shekhawat - 6 years, 2 months ago
Karan Shekhawat
Apr 10, 2015

How this equation is solve without using wolframalpha.....?

x 4 + 2 x 3 + x 2 2 x 1 = 0 x^4+2x^3+x^2-2x-1=0

Well, at least we have the same quartic polynomial. :) I posted a link to a solution method in my posted answer, but it is such a mess to go through all the steps I didn't think it was worth the effort just now. I'll wait to see if anyone has a more elegant approach before tackling this 'monster'.

Brian Charlesworth - 6 years, 2 months ago

Log in to reply

now that we got that, we have that:

1 + 2 x = x 2 + 2 x 3 + x 4 1+2x = x^2+2x^3+x^4 this suggests completing the square on the lefthandside. After doing that we get: ( 1 + x ) 2 = 2 x 2 ( 1 + x + x 2 ) x 4 (1+x)^2=2x^2(1+x+x^2)-x^4 then, passing the x^4 to the lhs adn dividing by x^2 (for its surely not zero) x 2 + ( 1 + 1 x ) 2 = 2 ( 1 + x + x 2 ) x^2+(1+\frac{1}{x})^2=2(1+x+x^2) but we got lucky because if we substract 2 ( 1 + x ) 2(1+x) we can complete the square in the lhs again because x ( 1 + 1 x ) = x + 1 x(1+\frac{1}{x})=x+1 and get ( x 1 1 x ) 2 = 2 x 2 (x-1-\frac{1}{x})^2=2x^2 and because ( x 1 1 x ) (x-1-\frac{1}{x}) is clearly negative we get the simple quadratic equation: x 1 1 x = x 2 x-1-\frac{1}{x}=-x\sqrt{2} which is straigthforward to solve.

Héctor Andrés Parra Vega - 6 years, 2 months ago

Log in to reply

This is really clever, Héctor; thanks for showing me the steps. Solving the last quadratic yields

x = 1 + 5 + 4 2 2 ( 1 + 2 ) , x = \dfrac{1 + \sqrt{5 + 4\sqrt{2}}}{2(1 + \sqrt{2})},

which at first didn't look like the posted solution, but they are in fact equal. :)

Brian Charlesworth - 6 years, 2 months ago

Log in to reply

@Brian Charlesworth Brian, thank you for your kind comment. You can get the answer proposed directly by, when you get the quadratic equation in standard form, multiplying all by 2 1 \sqrt{2}-1 and so you obtain 1 as the director coefficient.

Héctor Andrés Parra Vega - 6 years, 2 months ago

Log in to reply

@Héctor Andrés Parra Vega Yes. It is so nice! Thanks. I did not understand your first comment .Things are clear now.

Niranjan Khanderia - 6 years, 2 months ago

Log in to reply

@Niranjan Khanderia Thanks to you too :)

Héctor Andrés Parra Vega - 6 years, 1 month ago

In response to Brian Charlesworth: Two of the roots are reciprocal of one another as we see from the symmetry of coefficients. How can we use this fact ? These are the only real roots. But how do we know this?

Niranjan Khanderia - 6 years, 2 months ago

Log in to reply

That's interesting. If α \alpha is a solution, then when I plug in x = 1 α x = \frac{1}{\alpha} and then multiply through by α 4 -\alpha^{4} I end up with the equation α 4 + 2 α 3 α 2 2 α 1 = 0 , \alpha^{4} + 2\alpha^{3} - \alpha^{2} - 2\alpha - 1 = 0, which differs from the original equation in the sign for the squared term. So I don't think that in this case the two real roots are reciprocals of one another.

Brian Charlesworth - 6 years, 2 months ago

Log in to reply

@Brian Charlesworth I am very sorry. I made mistake in writing down the equation as
x 4 2 x 3 + x 2 2 x + 1. x^4-2x^3+x^2-2x+1.

Niranjan Khanderia - 6 years, 2 months ago

As I do always, I used graphing calculator TI 83 Plus and graph the polynomial. I kept the window, X..[.5,.6], Y,[-1E-4, 1E-4] , scales 1E-4 after locating the point in [-10,10],[-10,10], scales 1 and knowing x<1. The answer was good to third place of decimal from the given options. One can get even better by using ENTRY key{2nd ENTER} and the given function after knowing approximately by graphing.

Niranjan Khanderia - 6 years, 2 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...